Mechanistic insights into reductive deamination with hydrosilanes catalyzed by B(C6F5)3: A DFT study - Zhou, Miaomiao; Wang, Ting; Cheng, Gui-Juan (Frontiers in Chemistry, 2022)
Selective defunctionalization of synthetic intermediates is a valuable approach in organic synthesis. Here, we present a theoretical study on the recently developed B(C6F5)3/hydrosilane-mediated reductive deamination reaction of primary amines. Our computational results provide important insights into the reaction mechanism, including the active intermediate, the competing reactions of the active intermediate, the role of excess hydrosilane, and the origin of chemoselectivity. Moreover, the study on the substituent effect of hydrosilane indicated a potential way to improve the efficiency of the reductive deamination reaction.